2020
DOI: 10.1074/jbc.ra119.012320
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas aeruginosa exoenzyme Y directly bundles actin filaments

Abstract: Pseudomonas aeruginosa uses a type III secretion system (T3SS) to inject cytotoxic effector proteins into host cells. The promiscuous nucleotidyl cyclase, exoenzyme Y (ExoY), is one of the most common effectors found in clinical P. aeruginosa isolates. Recent studies have revealed that the nucleotidyl cyclase activity of ExoY is stimulated by actin filaments (F-actin) and that ExoY alters actin cytoskeleton dynamics in vitro, via an unknown mechanism. The actin cytoskeleton plays an important role in numerous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…Consequently, it causes irreversible actin microtubule disassembly, cell necrosis, and alteration of endothelial barrier integrity, following lung injury and end-organ dysfunction [ 120 , 122 ]. Recently, it was shown that ExoY possesses one actin-binding site that directly bundles actin filaments in the host cell [ 123 ]. Strikingly, ExoY downregulates the activation of transforming growth factor β-activated kinase 1 (TAK1), thereby inhibiting the production of proinflammatory cytokines by both macrophages and epithelial cells [ 124 ].…”
Section: Pseudomonas Aeruginosa Virulence Factomentioning
confidence: 99%
“…Consequently, it causes irreversible actin microtubule disassembly, cell necrosis, and alteration of endothelial barrier integrity, following lung injury and end-organ dysfunction [ 120 , 122 ]. Recently, it was shown that ExoY possesses one actin-binding site that directly bundles actin filaments in the host cell [ 123 ]. Strikingly, ExoY downregulates the activation of transforming growth factor β-activated kinase 1 (TAK1), thereby inhibiting the production of proinflammatory cytokines by both macrophages and epithelial cells [ 124 ].…”
Section: Pseudomonas Aeruginosa Virulence Factomentioning
confidence: 99%
“…Pa -ExoY can indeed alter F-actin turnover independently of its NC activity in Pa -ExoY-transfected epithelial cells [ 17 ]. Consistent with effects observed in cells, an inactive variant of Pa -ExoY inhibits the acceleration of F-actin disassembly induced by the regulatory ABP ADF (actin-depolymerizing factor)/cofilin in vitro [ 17 ] or can induce F-actin bundling in vitro [ 99 ]. Our recent biochemical studies of Vn -ExoY have also shown that its interaction with free or profilin-bound actin affects actin self-assembly dynamics in vitro independently of the NC activity of this toxin [ 101 ].…”
Section: Actin-activated Bacterial Toxinsmentioning
confidence: 82%
“…RID-mediated inactivation of Rac1 leads to actin cytoskeleton disruption and inhibits, together with ABH, pro-inflammatory response [ 98 ]. ExoY may also impact actin self-assembly [ 17 , 99 ]. ACD induces the formation of toxic actin monomers [ 23 , 100 ] that will lead, together with RID, to a disruption of tight junctions (TJ).…”
Section: Figurementioning
confidence: 99%
“…Further investigations are needed to see whether the formation of such a Vn-ExoY:G-actin:profilin abortive ternary complex for barbed-end elongation, which can be recruited by PRMs of elongation factors or other modular ABPs, may also contribute to Vn-ExoY cytotoxicity in host cells independently of its NC activity. Several observations suggest that Pa-ExoY may also affect eukaryotic target cells independently of its enzymatic activity (5,41,42). The interaction of Vn-ExoY with actin:profilin may be especially important for its subcellular localisation and activation at regions of active actin cytoskeleton remodelling, where G-actin:profilin and elongation-promoting factors such as formin or VASP together play important roles (40,(43)(44)(45).…”
Section: Discussionmentioning
confidence: 99%